2010
DOI: 10.1002/rsa.20339
|View full text |Cite
|
Sign up to set email alerts
|

Convergence to equilibrium of biased plane Partitions

Abstract: ABSTRACT:We study a single-flip dynamics for the monotone surface in (2 + 1) dimensions obtained from a boxed plane partition. The surface is analyzed as a system of non-intersecting simple paths. When the flips have a non-zero bias we prove that there is a positive spectral gap uniformly in the boundary conditions and in the size of the system. Under the same assumptions, for a system of size M, the mixing time is shown to be of order M up to logarithmic corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For one thing, macroscopic shapes in this case minimize not the free energy but the free energy with a volume constraint, and the mixing time turns out to scale like δ −1+o(1) rather than δ −2+o(1) . We refer to [LL19] for the ASEP in an interval (the authors prove the sharp estimate T mix ∼ cδ −1 , as well as the occurrence of the cut-off phenomenon) and to [CMT11,GPR09] for a dynamics of biased plane partitions, which is a lozenge tiling dynamics where the two updates of Figure 1.2 have different transition rates p and q. Also in the latter case, the result is that T mix = δ −1+o(1) (see [GPR09], where this is proven for small enough bias log(p/q), and [CMT11] for the general case of arbitrary non-zero bias).…”
Section: The Broader Contextmentioning
confidence: 99%
“…For one thing, macroscopic shapes in this case minimize not the free energy but the free energy with a volume constraint, and the mixing time turns out to scale like δ −1+o(1) rather than δ −2+o(1) . We refer to [LL19] for the ASEP in an interval (the authors prove the sharp estimate T mix ∼ cδ −1 , as well as the occurrence of the cut-off phenomenon) and to [CMT11,GPR09] for a dynamics of biased plane partitions, which is a lozenge tiling dynamics where the two updates of Figure 1.2 have different transition rates p and q. Also in the latter case, the result is that T mix = δ −1+o(1) (see [GPR09], where this is proven for small enough bias log(p/q), and [CMT11] for the general case of arbitrary non-zero bias).…”
Section: The Broader Contextmentioning
confidence: 99%
“…There is a well-studied height function that maps hexagonal lozenge tilings bijectively to plane partitions lying in an n × n × n box (see, e.g., [25]), and it follows that lozenge tilings with a fixed average height of k are precisely the plane partitions with volume k. The Markov chain that adds or removes single cubes on the surface of the plane partition (corresponding to rotating three nested lozenges 180 degrees) is known to mix rapidly in the unbiased case. Caputo et al [7] studied the biased version of this chain with a preference toward removing cubes, and showed that this chain converges in O(n 3 ) time.…”
Section: Lozenge Tilings With Fixed Average Heightmentioning
confidence: 99%
“…In this paper we prove that the mixing time is O(n log n) as long as the spectral gap of the process is Ω(1). Our technique bares some similarities to those employed in [6] to analyse the Glauber dynamics of biased plane partitions.…”
Section: Introductionmentioning
confidence: 99%